2021
DOI: 10.2147/ppa.s330371
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Utility Analysis of a Medication Adherence Management Service Alongside a Cluster Randomized Control Trial in Community Pharmacy

Abstract: Background It is necessary to determine the cost utility of adherence interventions in chronic diseases due to humanistic and economic burden of non-adherence. Purpose To evaluate, alongside a cluster-randomized controlled trial, the cost-utility of a pharmacist-led medication adherence management service (MAMS) compared with usual care in community pharmacies. Materials and Methods The trial was conducted over six months. Patients with treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…For example, a systematic review of interventions adopted in asthma management found that all of the assessed MAEIs were cost-effective considering the increased adherence rate, improved clinical effectiveness and the reduced costs of asthma care ( Khaw et al, 2021 ). Similarly, the cost of a pharmacist-led medication adherence management service for chronic patients was estimated to be €27.33 ± 0.43 per patient for 6 months, which resulted in an incremental cost-utility ratio (ICUR) of €2,086.30/QALY, thus proving that the intervention was time-consuming, yet cost-effective ( Valverde-Merino et al, 2021 ). In another study, despite increased drug costs, better medication adherence was assessed as cost-effective in chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a systematic review of interventions adopted in asthma management found that all of the assessed MAEIs were cost-effective considering the increased adherence rate, improved clinical effectiveness and the reduced costs of asthma care ( Khaw et al, 2021 ). Similarly, the cost of a pharmacist-led medication adherence management service for chronic patients was estimated to be €27.33 ± 0.43 per patient for 6 months, which resulted in an incremental cost-utility ratio (ICUR) of €2,086.30/QALY, thus proving that the intervention was time-consuming, yet cost-effective ( Valverde-Merino et al, 2021 ). In another study, despite increased drug costs, better medication adherence was assessed as cost-effective in chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic conditions, such as hypertension, diabetes, asthma, and chronic obstructive pulmonary disease (COPD), face a heightened risk of non-adherence, with estimated rates of 50% for hypertension, 50-60% for asthma, and 70% for COPD (9).…”
Section: Hlavní Témamentioning
confidence: 99%
“…This service improves patients' ability to optimize medication management. A Spanish study showed the effectiveness of the service for improving medication adherence, clinical outcomes 35 and quality of life 36 for patients suffering hypertension, asthma and chronic obstructive pulmonary disease. The service is not remunerated by the SNS nor any regional health system; however, a tool for improving adherence (dose administration aids) is remunerated locally in Galicia for patients over 74 years old with over 13 different medications who live alone.…”
Section: Community Pharmacy Services Related To Self-care In Spainmentioning
confidence: 99%